Байгалийн цацраг идэвхийг Монголд судалсан байдлаас - Д, Шагждамба; Н, Норов (Scientific transaction of the National University of Mongolia. Physics, 2022)
In this paper evaluated results of a study of natural radioactivity in Mongolia. As well important trends of the study was established and identified ways of improvement of this study in future was discussed.